GE_GERICHTE C/26584/2017 vom 12. Februar 2019 - GE Cour de justice (2019)
SÉQUESTRE(LP);SUSPENSION DE LA PROCÉDURE;PIERRE PRÉCIEUSE;ENCHÈRES;DROIT ISLAMIQUE | LP.278.al3; LP.271.al1.ch4; LP.278; LP.273.al1